Applying innovative approach "Nature of Science (NoS) within inquiry" for developing scientific literacy in the student worksheet - Widowati, A; Anjarsari, P; Zuhdan, K P; Dita, A (Journal of physics. Conference series, 2018)
The challenges of the 21st century require innovative solutions. Education must able to make an understanding of science learning that leads to the formation of scientific literacy learners. This research was conducted to produce the prototype as science worksheet based on Nature of Science (NoS) within inquiry approach and to know the effectiveness its product for developing scientific literacy. This research was the development and research design, by pointing to Four D models and Borg & Gall Model. There were 4 main phases (define, design, develop, disseminate) and additional phases (preliminary field testing, main product revision, main field testing, and operational product revision). Research subjects were students of the junior high school in Yogyakarta. The instruments used included questionnaire sheet product validation and scientific literacy test. For the validation data were analyzed descriptively. The test result was analyzed by an N-gain score. The results showed that the appropriateness of worksheet applying NoS within inquiry-based learning approach is eligible based on the assessment from excellent by experts and teachers, students' scientific literacy can improve high category of the N-gain score at 0.71 by using student worksheet with Nature of Science (NoS) within inquiry approach.